Gender and financial management practices in selected private schools of Rizal Province - Yokomori, Rosalinda Banzuela (2008)
This study described the financial management practices in the generation, allocation, and utilization of school resources of selected male and female school administrators in the province of Rizal. It also presented the similarities and the differences in these practices and the factors that account for these similarities and differences as well as the relationship of gender to the respondents' management practices. There were 20 selected respondents and the mixed methods research design was employed. Findings showed that male and female administrators perform varied practices in the generation, allocation, and utilization of their school resources. Government laws and school policies are major factors for the similarities and differences while gender and economic reasons are supporting factors.
Thesis (M.A. Educational Administration)--University of the Philippines, Diliman.
Keywords: Education, Secondary -- Philippines -- Rizal -- Finance; Private school -- Philippines -- Rizal -- Finance; School administrators -- Philippines -- Rizal; School management and organization -- Philippines -- Rizal; Sex differences in education -- Philippines -- Rizal; Sex role in the work environment -- Philippines -- Rizal